TSH concentrations in parents and their offspring: a cross-sectional family-based analysis. Issue 6 (26th November 2021) - Girschik, Carolin; Drogge, Sophie-Charlotte; Kowall, Bernd; Lehmann, Nils; Stang, Andreas; Zwanziger, Denise; Erbel, Raimund; Führer, Dagmar; Jöckel, Karl-Heinz
Abstract : Objective: Studies that evaluated the genetic influences on thyroid-stimulating hormone (TSH) concentrations were primarily performed in twin cohorts. The aim of this study was to investigate the sex-specific association of serum TSH concentrations between parents and their offspring. Methods: We used data from the population-based Heinz Nixdorf Recall Study and the associated MultiGeneration Study, including offspring and their biological parents. In 3115 participants (including 1558 offspring from 1138 families), self-reported thyroid diseases and median TSH concentrations depending on thyroid status were assessed. Familial associations of TSH concentrations were investigated in 1485 healthy subjects using linear regression modeling in each group of the parent–offspring relationship using the parent's TSH concentration as the exposure of interest. To account for the family effect, a mixed‐effects ordinal logistic regression model with random intercept varying at the family level was fitted, using the TSH concentration of the offspring classified into sex- and age-specific quartiles as the outcome. Results: For every 1 mIU/L increase in the mother's or father's TSH concentration, the daughter's TSH concentration increases by 0.13 mIU/L (95% CI: −0.01; 0.27) and 0.19 mIU/L (0.05; 0.33), respectively, and the son's TSH concentration increases by 0.13 mIU/L (0.02; 0.25) and 0.20 mIU/L (0.08; 0.32), respectively. Further sensitivity analyses by expanding inclusion criteria and taking family clustering into account corroborated these results. Conclusions: Serum TSH concentrations of parents are positively associated with those of their offspring in all sex-specific relationships.